Prospek dan Tantangan Implementasi Ecosystem-based Fisheries Management di Pesisir Indonesia - Ahmad Nur Fadhli; Syahrial Maulana; Fadel Fadel (Al-Buhuts, 2025)
Conventional fisheries management in Indonesia often disregards ecosystem sustainability, leading to problems such as overfishing and environmental degradation in Indonesian waters. In response, this review study aims to analyze the prospects and challenges of implementing the Ecosystem-based Fisheries Management (EBFM) model in Indonesia's coastal ecosystems, based on relevant literature. Through a synthesis of various case studies, this review finds that EBFM has excellent prospects as a solution for achieving sustainable fisheries management. This model has the potential to increase fisheries productivity and contribute positively to the Gross Domestic Product (GDP), while also improving the welfare of fishermen. However, the implementation of EBFM faces significant challenges, including infrastructure limitations such as stagnant fishing ports, a lack of coordination among stakeholders, and the traditional socio-economic characteristics of fishermen. Overall, EBFM is a promising approach, but its success is highly dependent on the readiness and commitment of all parties to overcome these challenges.